2021
DOI: 10.1111/coa.13823
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning‐based model for prediction of outcomes in palatal surgery for obstructive sleep apnoea

Abstract: Many surgical techniques have been devised to treat snoring. One of them is the uvulopalatal flap (UPF) technique which removes only the mucous membrane of the palate and uvula.Palatal muscle resection (PMR) is a procedure where the levator veli palatini or palatoglossus muscle is cut, and a simple short anastomosis is performed. The purpose of this study was to determine, through state-of-the-art machine learning (ML) techniques, which factors influence the success of surgery in patients who had been operated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The study identified that the ML model with the highest accuracy was lasso logistic regression. The small sample size of 29 patients was a limiting factor in this study, and influenced which ML model was most accurate as the small data set compared to number of variables regularization methods are typically most useful [ 30 ].…”
Section: Main Textmentioning
confidence: 99%
“…The study identified that the ML model with the highest accuracy was lasso logistic regression. The small sample size of 29 patients was a limiting factor in this study, and influenced which ML model was most accurate as the small data set compared to number of variables regularization methods are typically most useful [ 30 ].…”
Section: Main Textmentioning
confidence: 99%